2007
DOI: 10.3758/bf03194024
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in object location memory: A meta-analysis

Abstract: The goal of the present study was to quantify the magnitude of gender differences in object location memory tasks. A total of 123 effect sizes (d) drawn from 36 studies were included in a meta-analysis using a hierarchical approach. Object identity memory (37 effect sizes) and object location memory (86 effect sizes) tasks were analyzed separately. Object identity memory task showed significant gender differences that were homogeneous and in favor of women. For the object location memory tasks, effect sizes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
168
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 69 publications
16
168
2
3
Order By: Relevance
“…28, for White, non Hispanics -d = .33) is similar to several published studies (d = .19-.22), with those having a smaller sample (n = 29) not finding a sex difference and those with a larger sample (n = 196) reporting a significant difference (Lutchmaya et al, 2004;Williams et al, 2003). Similarly, the female advantage in location memory is small (d = .26) (Voyer et al, 2007), consistent with the general finding that sex differences in female-linked tasks compared to male-linked tasks generally yield smaller effects (Hyde & Linn, 1988). Thus, it is likely that our non-significant sex difference in 2D: 4D ratio and object location memory is related to considerations external to the hypothesized effect (i.e., sample size; Thompson, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…28, for White, non Hispanics -d = .33) is similar to several published studies (d = .19-.22), with those having a smaller sample (n = 29) not finding a sex difference and those with a larger sample (n = 196) reporting a significant difference (Lutchmaya et al, 2004;Williams et al, 2003). Similarly, the female advantage in location memory is small (d = .26) (Voyer et al, 2007), consistent with the general finding that sex differences in female-linked tasks compared to male-linked tasks generally yield smaller effects (Hyde & Linn, 1988). Thus, it is likely that our non-significant sex difference in 2D: 4D ratio and object location memory is related to considerations external to the hypothesized effect (i.e., sample size; Thompson, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with previous research (Lambourne, 2006;Rahman et al, 2011) and are inconsistent with Kaufman (2007). Research showed male advantage in the spatial visualization and mantel rotation tests further more researches cited by Harness et al (2008) and Voyer et al (2007) demonstrated that female advantage on the visual working-memory task and showed significantly greater recall than men. In this study male and female subjects did not differ in either in intrusion errors or serial length or switch (colour) in and working memory.…”
Section: Discussionsupporting
confidence: 80%
“…Study cited by Johnson and Bouchard (2007) showed that women displaying generally greater memory than male. On the other hand Voyer et al (2007) indicted that Females are somewhat more accurate in specific areas such as Memory for object locations in adolescent and adult samples, whereas other indicated that men tend to be more accurate in memory for visuospatial stimuli that are highly complex (Lewin et al, 2001). Study by Loring-Meier and Halpern (1999) found that males responded more quickly on all four tasks than women in making spatial judgments based on mental images.…”
Section: Introductionmentioning
confidence: 96%
“…Based on empirical evidence showing that males usually perform better on spatial working memory tasks (Duff & Hampson, 2001;Lejbak, Vrbancic, & Crossley, 2009;Ramos-Loyo & Sanchez-Loyo, 2011;Voyer, Postma, Brake, & Imperato-McGinley, 2007) one of the initial hypotheses of the present study was that regardless the length of the sequence, males would achieve a higher number of correct responses than females. Although this assumption was fulfilled in general, more detailed assessment of the experimental results showed that males did indeed perform significantly better than females, but only while reproducing longer sequences.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that females recall better the appearance of others better than males (Mast & Hall, 2006) and score higher on tasks involving manipulation of phonological and semantic information, episodic and semantic memory, verbal learning, verbal analytical working memory (WM), object location memory, fine motor skills and perceptual speed, while males tend to score higher on tasks involving visuospatial working memory (VSWM), fluid reasoning, and positional reconstruction, or when spatiotemporal analyses are required (Duff & Hampson, 2001;Halpern, 1997;Kramer, Delis, Kaplan, O'Donnell, & Prifitera, 1997;Lejbak, Vrbancic, & Crossley, 2009;Maitlan, Herlitz, Nyberg, Bäckman, & Nilsson, 2004;Postma, Winkel, Tuiten, & van Honk, 1999;Ramos-Loyo & Sánchez-Loyo, 2011;Voyer, Postma, Brake, & Imperato-McGinley, 2007).…”
mentioning
confidence: 99%